Influence of Blending of Diesel Certified and Biodiesel CPO on Efficiency of 60 MMT SB Boiler Type - Novia Sumardi; Ellyanie Ellyanie; Rosdiana Moeksin (Universitas Sriwijaya, 2013)
Abstract Combustion is the process of mixing oxygen and carbon in speed and produces heat. Oxygen from the air, while carbon derived from fuel. Combustion boilers as a chemical process of unification of the fuel and oxygen from the air with the speed of a particular reaction that produces energy. Calculation of the combustion process is the starting point the design of boilers, furnaces and other appliances that generate heat from the combustion process derived from the number of elements involved in a chemical reaction, the amount of heat generated and the efficiency of combustion. The fuel is a mixture of diesel and biodiesel certified crude palm oil, ratio B0, B5, B10, B15, B20, B30 testing using Fire Tube BoilersSB60MMT. From the ultimate analysis and dry flue gas emissions (gas Analyzer), then calculated based on stoichiometric combustion and efficiency using the indirect method, the calculation results obtained from the more mixed crude palm oil biodiesel is added then the content of SO2, CO, NOx increasingly reduced. Also obtained the largest heat loss due to dry flue gas and 8,209% heat loss due to evaporation of water formed in H2 fuel efficiency of 7,002% to 85.637% on the blend B20. Keywords: Solar Certified, CPO Biodiesel, Fire Tube Boilers, Emissions, Effici